NCOG-44. NEUROLOGIC ASSESSMENT IN NEURO-ONCOLOGY (NANO) SCALE IN A PHASE II STUDY OF PEMBROLIZUMAB OR PEMBROLIZUMAB PLUS BEVACIZUMAB IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (9th November 2020) - Nayak, Lakshmi; Molinaro, Annette; Peters, Katherine; Clarke, Jennifer; Jordan, Justin; de Groot, John; Nghiemphu, Phioanh; Kaley, Thomas; Colman, Howard; McCluskey, Christine; Gaffey, Sarah; Smith, Timothy; et al.
Abstract: PURPOSE: The neurologic assessment in neuro-oncology (NANO) scale was developed as a standardized metric to objectively measure neurologic function in brain tumor patients to complement radiographic assessment in defining overall outcome. A multicenter, phase 2 study of pembrolizumab with or without bevacizumab in patients with recurrent glioblastoma incorporated the NANO scale as an exploratory endpoint. METHODS: Neurologic examination was evaluated at baseline and MRI assessments using the NANO scale until patients came off study. Statistical descriptive data analysis was performed using R (version 3.4.3). Correlation analysis utilized Fisher's exact test. RESULTS: NANO compliance rate was 94% in 80 patients accrued on the study. Of the 80 patients, 7 were missing NANO at baseline visit and were excluded from analysis for NANO response criteria. Fifteen patients did not have end of treatment NANO evaluation. Of 73 patients, 35 (48%) had a normal neurologic examination at baseline by NANO. Strength and language accounted for the majority of changes in neurologic function over the course of study treatment. Eighteen patients (25%) had neurologic progression by NANO, of whom 2 did not have concurrent radiographic progression. Three patients (pembrolizumab plus bevacizumab cohort) had a neurologic response associated with stable disease on MRI. NANO assessment prior to initiation of cycle 3 correlated with RANO response (p=0.011), change in KPS (p=0.002) and dexamethasone requirement (p=0.007) while those with NANO progression at this assessment had worse overall survival (291 vs 324 days), but this trend did not achieve statistical significance (p=0.2). CONCLUSIONS: Evaluation of neurologic function by NANO scale was feasible in a multicenter prospective study in patients with GBM with a high compliance rate. The NANO scale objectively tracked stable neurologic function in most patients throughout the trial period and was associated with a trend for survival.